2014
DOI: 10.1038/ajg.2014.158
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to Mesalamine Questionnaire: A Novel Tool to Predict Mesalamine Nonadherence in Patients with IBD

Abstract: Patients' beliefs about the need for maintenance mesalamine and their concerns about side effects influence their adherence to mesalamine over time. These concerns could easily be raised in practice to identify patients at risk of nonadherence (Clinical Trial number NCT01349504).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In practical studies, barriers to medication adherence are usually presented as a series of single factors without a definite classification (Moss et al, 2014;Müller et al, 2015;Newman-Casey et al, 2015;Xavier et al, 2016). The common barriers to medication adherence for CVD include unaffordable costs, lack of belief in the necessity of medication, side effects of medication or medication concerns, complex regimens, forgetfulness, lack of family or social support, depression, lack of disease knowledge, and inconvenient access to medications or care (Choudhry et al, 2011;Nair et al, 2011;Müller et al, 2015;Zullig et al, 2015;Banerjee et al, 2016;Crawshaw et al, 2016;Xavier et al, 2016;Wang et al, 2019).…”
Section: Detecting Barriers To Medication Adherencementioning
confidence: 99%
“…In practical studies, barriers to medication adherence are usually presented as a series of single factors without a definite classification (Moss et al, 2014;Müller et al, 2015;Newman-Casey et al, 2015;Xavier et al, 2016). The common barriers to medication adherence for CVD include unaffordable costs, lack of belief in the necessity of medication, side effects of medication or medication concerns, complex regimens, forgetfulness, lack of family or social support, depression, lack of disease knowledge, and inconvenient access to medications or care (Choudhry et al, 2011;Nair et al, 2011;Müller et al, 2015;Zullig et al, 2015;Banerjee et al, 2016;Crawshaw et al, 2016;Xavier et al, 2016;Wang et al, 2019).…”
Section: Detecting Barriers To Medication Adherencementioning
confidence: 99%
“…In addition, recognizing that poor adherence to mesalamine is common, Moss et al 45 developed a 10-item survey to assesses UC patient-reported barriers to mesalamine adherence and predict those at risk for future non-adherence. They found that patients' beliefs about the need for maintenance mesalamine and their concerns about side effects influenced their adherence to mesalamine over time.…”
Section: Factors Associated With Non-adherencementioning
confidence: 99%
“…3,4 Unfortunately, adherence to mesalamine regimens in general is poor, particularly when patients are in remission. 5,6 Nonadherence to mesalamine has negative implications for patients and the health care system; relapse rates, colorectal cancer prevalence, and health care costs are all greater in nonadherent patients than adherent ones. [7][8][9][10] Many patients report that their nonadherence with oral mesalamine is unintentional, e.g., they forget to take the pills.…”
mentioning
confidence: 99%